2015
DOI: 10.1007/s10266-015-0207-4
|View full text |Cite
|
Sign up to set email alerts
|

Evaluation of dental implants as a risk factor for the development of bisphosphonate-related osteonecrosis of the jaw in breast cancer patients

Abstract: It remains unclear whether dental implants are a risk factor for the development of bisphosphonate-related osteonecrosis of the jaw (BRONJ). We retrospectively evaluated the status of dental implants in patients given intravenous bisphosphonates (BPs) in a breast cancer cohort to elucidate the risk for BRONJ at the implant site. We established a BRONJ oral monitoring program for 247 breast cancer patients given intravenous BP in our institution. The 3-year cumulative incidence rate was determined. The systemic… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

0
25
0

Year Published

2016
2016
2022
2022

Publication Types

Select...
9

Relationship

0
9

Authors

Journals

citations
Cited by 29 publications
(25 citation statements)
references
References 39 publications
0
25
0
Order By: Relevance
“…Recent reports suggest that implants inserted before patients with cancer or osteoporosis are treated with BPs are unlikely associated with subsequent occurrence of BRONJ if oral health is appropriately managed [25,26]. However, dental implantation performed during or after BP treatment is a potential risk factor for BRONJ.…”
Section: ) Dental Implants and Aronjmentioning
confidence: 99%
“…Recent reports suggest that implants inserted before patients with cancer or osteoporosis are treated with BPs are unlikely associated with subsequent occurrence of BRONJ if oral health is appropriately managed [25,26]. However, dental implantation performed during or after BP treatment is a potential risk factor for BRONJ.…”
Section: ) Dental Implants and Aronjmentioning
confidence: 99%
“…The systematic review by Guazzo et al 16 similarly stated that, because of study heterogeneity and the high risk of bias, insufficient data quality did not allow estimates of risk to be determined. Matsuo et al 17 and Tallarico et al 18 reported no increased risk in failure associated with IV or oral bisphosphonate use, respectively. The association between oral bisphosphonate use and dental implant failure was investigated in a case-control study involving 337 female patients (age ࣙ40 years).…”
Section: Bisphosphonatesmentioning
confidence: 97%
“…Reason for exclusion Stvrtecky, Kaufman, and Borgetti, (1995) Only 9 patients Marx, Sawatari, Fortin, and Broumand (2005) Only 4 Famili and Zavoral (2015) Only 3 patients with relevant medication intake Nisi et al (2015) Only 9 patients with MRONJ associated with implants Rugani, Kirnbauer, Acham, Truschnegg, and Jakse (2015) Single case report Matsuo et al (2016) Only 6 patients Gurgel et al (2017) Patients with BP and/or HRT intake not reported separately Wagner et al (2017) Only 5 patients with BP intake…”
Section: Appendix 1 Information Sources and Literature Searchmentioning
confidence: 99%